Reasons for Migration of Armenians in the Ottoman Empire before 1915 - Ozkan, Selim Hilmi (BRILL, 2020)
Migration has been common throughout human history and has been part of Armenian history for many centuries in varying degrees. However, at the end of the 19th century and in the early years of the 20th century, Armenians experienced an unprecedented rate of migration. The large outflow caused complications that affected many aspects of the social life of Armenians. They had lived in peace throughout the Anatolian territory without any geographical limitations until the last period of the Ottoman Empire when they began to be radicalized by some countries that wished to make Christian Armenians and Muslims enemies. Consequently, Armenians started to migrate abroad from Anatolia. This article examines the reasons for the migration of the Ottoman Armenians before World War I by reference to Ottoman archival documents.
Keywords: Ottoman Empire; Armenian; migration; Armenian migration; Area Studies